Multi-robot Control via Smart Phone and Navigation in Robot Operating System - Khadir BESSEGHIEUR; Wojciech KACZMAREK; Jarosław PANASIUK (Problemy Mechatroniki)
Robot Operating System (ROS) is an open source robot software framework which provides several libraries and tools to easily conduct different robot applications like autonomous navigation and robot teleoperation. Most of the available packages across the ROS community are addressed for controlling a single robot. In this paper, we aim to extend some packages so, they can be used in multi-robot applications on ROS. Mainly, the multi-robot autonomous navigation and multi-robot smart phone teleoperation are addressed in this work. After being extended and compiled, the new packages are assessed in some simulations and experiments with real robots.